(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
In the article, dignitonyms and faleronyms, which are a part of our heritage, were actively used in their time, archaism today, and document linguistic research.